Culturally valuable minority crops provide a succession of floral resources for flower visitors in traditional orchard gardens - Norfolk, Olivia; Eichhorn, Markus P.; Gilbert, Francis (Springer Verlag, 2014)
Agricultural intensification typically has detrimental effects on pollinator communities, but diverse cropping systems that contain sequentially-flowering crops have the potential to benefit pollinators through the provision of additional floral resources. In this study we investigate the importance of cultivated flora for flower visitors in ten agricultural gardens in South Sinai, Egypt. Insect-flower interactions in gardens and unmanaged plots were surveyed across a four-month period in two environmentally distinct years (pre-flood and post-flood). Despite containing an equal abundance and diversity of wild plants as unmanaged habitat, gardens supported a higher abundance and diversity of flower visitors due to the additional presence of cultivated flora. Visitation networks exhibited dramatic intra-annual changes in composition, with cultivated plants becoming increasingly important in later months. Trends were highly conserved across 2 years despite highly contrasting rainfall. Several key crop species were strongly involved in shaping the structure of the networks, the majority of which were herbs with strong cultural significance (fennel, rosemary, mint) and grown incidentally alongside the primary orchard crops. Minority crops are frequently overlooked in agricultural systems due to their low economic value, but we show that they can have a dramatic influence upon the structure of visitation networks, increasing both pollinator abundance and diversity, and emphasising the link between cultural practices and biodiversity conservation.